ТЕКСТ НА НАРОДЕН МАКЕДОНСКИ ЈАЗИК СО ГРЧКИ БУКВИ ОД 1868 ГОДИНА ЗА НАЧИНОТ НА ВЕНЧАВАЊЕ - Славчо Ковилоски (Институт за македонска литература, 2016)
The use of the Greek alphabet when writing letters, notifications, and various announcements in the vernacular Macedonian is a phenomenon characteristic of the Macedonian region throughout the 19th century. One example of a text written with Greek letters in the vernacular Macedonian of the Ohrid-Struga region is the announcement of wedding ceremony procedures, (Epistolia/book) consisting of seven items, issued by the Greek Metropolis of Ohrid to the faithful. The content of the announcement addressed to all priests in the areas of Drimkol, Prespa, and Ohrid was of great importance for the regulation of duties when getting married. Hence, it is of great importance for the establishing of church canons, i.e. rituals of the Christian population living in the aforementioned areas in the second half of the 19th century, as well as the male-female relations in this period.
Keywords: wedding procedures, Greek letters, the vernacular Macedonian, announcement, letter, Ecumenical Patriarchate.